PENGARUH PERGANTIAN MANAJEMEN, FINANCIAL DISTRESS DAN OPINI AUDIT TERHADAP PUBLIC ACCOUNTANT SWITCHING DENGAN VARIABEL PEMODERASI UKURAN PERUSAHAAN (EMITEN BASIC MATERIALS DI BURSA EFEK INDONESIA PERIODE 2021-2023) - Wijayanti, Yulia; Mukti, Aloysius Harry; Eprianto, Idel (SINERGI : Jurnal Riset Ilmiah, 2025)
This study aims to test and analyze the Effect of Management Change, Financial Distress and Audit Opinion on Public Accountant Switching with the Moderating Variable of Company Size. The population in this study is the Basic Materials Issuers of the Indonesia Stock Exchange for the 2021-2023 Period. The sampling technique used is the purposive sampling method and obtained 61 company samples. The analysis methods used are Descriptive Statistical Analysis, Logistic Regression Analysis, Hypothesis Testing and Moderation Regression Analysis. The results of this study indicate that partially Management Change has a positive effect on Public Accountant Switching and the variables Financial Distress and Audit Opinion do not affect Public Accountant Switching. The results of the study for the moderating variable, namely Company Size, are able to moderate (weaken) the positive effect of Management Change on Public Accountant Switching and Company Size is unable to moderate Financial Distress and Audit Opinion.